Prospek Pengendalian Terpadu Penyakit Lodoh pada Persemaian Tanaman Kehutanan - Achmad (Institut Pertanian Bogor (IPB University), 1999)
Damping-off is one of the diseases that decreases the seedling quantity of most forest trees. Up till now, control of damping-off by using fungicides is widely applied. However, excessive usage of fungicides is harmful for human beings, animals, as well as environment. Integrated management is expected to be applied in managing damping-off on forest-tree seedlings. This prospect is shown by several choices of techniques to handle the disease other than chemical handling by using fungicides, as mentioned in this paper. However, efforts to make the prospect to be achieved are still needed. Focused and well-planned research must be done to combine compatible techniques to support integrated management of damping-off on forest-tree seedlings.